Analysis of generalized force and its influence on ride and stability of railway vehicle. (June 2020) - Sharma, Rakesh Chandmal; Sharma, Sakshi; Sharma, Sunil Kumar; Sharma, Neeraj
Formulation of a rail vehicle model using Lagrange's method requires the system's kinetic energy, potential energy, spring potential energy, Rayleigh's dissipation energy and generalized forces to be determined. This article presents a detailed analysis of generalized forces developed at wheel–rail contact point for 27 degrees of freedom–coupled vertical–lateral model of a rail vehicle formulated using Lagrange's method and subjected to random track irregularities. The vertical–lateral ride comfort of the vehicle and the ride index of the vehicle are evaluated based on ISO 2631-1 comfort specifications and stability is determined using eigenvalue analysis. The parameters that constitute the generalized forces and critically influence ride and stability have been identified and their influences on the same have been analysed in this work.